THE EFFECT OF PRICE, PROMOTION AND QUALITY OF SERVICE ON GO-JEK CUSTOMER SATISFACTION (CASE STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS UNIVERSITY OF MUHAMMADIYAH NORTH SUMATRA) - Arda, Mutia; Maulana Banurea, Ahmad (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The purpose of this study was to determine and analyze prices, promotions, and service quality on go-jek customer satisfaction either partially or simultaneously. The approach used in this study is an associative approach. The population in this study were economic and business go jekusers, Muhammadiyah University of North Sumatra. The sample in this study using the Wibisono formula to collect 100students. Data collection techniques in this study used a questionnaire technique. The data processing in this study used the SPSS (Statistical Package for the Social Sciences) version 24.00 software program. The results of this study prove that partially and simultaneously analyzing prices,